Analyzing the Online Reading Strategies of Indonesian In-Service EFL Teachers - Laeli, Anita Fatimatul; Werdiningsih, Indah; Hanafi (JURNAL PENDIDIKAN DAN PENGEMBANGAN MANUSIA, 2025)
The rapid advancement of technology in the 21st century has transformed English language learning, particularly in reading activities. The shift from print to digital texts not only requires adapting traditional reading strategies but also introduces new strategies, such as searching for and synthesizing information online. This study examines the online reading strategies employed by English language teachers in East Java. Using a quantitative research design with a survey method, 97 English language teachers participated by completing the SLORSI (Second Language Online Reading Strategies Inventory) questionnaire. The results revealed that Traditional Cognitive Strategies, including inferring, skimming, and translating, were the most commonly used, with high scores across all subscales. In the New Cognitive Strategies dimension, strategies like locating, synthesizing, saving, and navigating were also frequently employed, with the saving strategy being the most dominant (Mean = 4.24). The Evaluation Strategy dimension indicated that teachers frequently assessed the credibility of online information. However, Communication Strategies were used the least (Mean = 3.33), particularly in terms of online collaboration and discussion. In conclusion, the study highlights that English language teachers effectively use a range of cognitive, evaluative, and communicative strategies in reading online texts. Nevertheless, there is potential for further development, particularly in enhancing communicative strategies. This underscores the importance of equipping teachers with the skills to navigate and critically engage with digital texts in their teaching practices.